Orphan Hereditary Syndromes in the Practice of Pediatric Endocrinologist - M.O. Ryznychuk; V.P. Pishak (Zaslavsky O.Yu., 2015)
Orphan syndromes - a group of diseases that are extremely rare, with an incidence of 10 cases per 100,000 people. Doctors in different fields should pay considerable attention to orphan syndromes with endocrine disorders. Phenotypically, these syndromes begin to manifest since birth or they occur in childhood. The article presents short phenotypic and genetic characteristics of certain orphan endocrine syndromes, such as Perlman, Proteus, Sotos 1, Sotos 2 and Berardinelli, which are associated with gigantism. Above-mentioned syndromes are caused by different gene mutations, namely Perlman syndrome - by homozygous or heterozygous mutation in DIS3L2 gene on the chromosome 2q37, Proteus syndrome - mutation in AKT1 gene on chromosome 14q32.3, Sotos syndrome 1 is caused by heterozygous mutation in NSD1 gene in the 5q35 region, Sotos syndrome 2 - by heterozygous mutation in NFIX gene on chromosome 19p13.3. Berardinelli syndrome, which is divided into four types, has four different mutations, namely: type 1 is caused by mutations in AGPAT2 gene in locus 9q34, type 2 - in BSCα2gene in locus 11q13, type 3 - by mutations in CAV1 gene (locus 7q31), type 4 - by mutation in PTRF gene located on the chromosome 17.